2001
DOI: 10.1046/j.0953-816x.2001.01810.x
|View full text |Cite
|
Sign up to set email alerts
|

Associative effects of Pavlovian differential inhibition of behaviour

Abstract: The associative inhibitory control of behaviour is a major component of Pavlovian learning theory, but little is known about its functional neuroanatomy. The associative effects of differential inhibition of conditioned behaviour were investigated by mapping learning-related changes in brain activity of the rat with fluorodeoxyglucose autoradiography. Of interest was how a tone is processed in auditory and extra-auditory systems of the rat brain under similar behavioural, but different associative conditions. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
12
0

Year Published

2004
2004
2014
2014

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 51 publications
1
12
0
Order By: Relevance
“…Cued conditioned group showed a relative CO activity decrease in the hippocampal regions examined, suggesting that changes in neural metabolism in this brain area associated with aversive auditory cued conditioning depend on the learned value of the tone CS. Our data is supported by other studies which also demonstrated a decrease in hippocampal CO activity following Pavlovian fear conditioning (Conejo et al, 2005), and conditioned response inhibition (Jones and Gonzalez-Lima, 2001). Additionally, local cerebral perfusion is decreased in response to a fear conditioned tone CS (Holschneider et al, 2006), and neurotoxic lesions of the dorsal hippocampus have been found to impair cued Pavlovian conditioning in rats (Maren et al, 1997), further indicating that dorsal hippocampus plays an important role in the Pavlovian fear conditioning in rats.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Cued conditioned group showed a relative CO activity decrease in the hippocampal regions examined, suggesting that changes in neural metabolism in this brain area associated with aversive auditory cued conditioning depend on the learned value of the tone CS. Our data is supported by other studies which also demonstrated a decrease in hippocampal CO activity following Pavlovian fear conditioning (Conejo et al, 2005), and conditioned response inhibition (Jones and Gonzalez-Lima, 2001). Additionally, local cerebral perfusion is decreased in response to a fear conditioned tone CS (Holschneider et al, 2006), and neurotoxic lesions of the dorsal hippocampus have been found to impair cued Pavlovian conditioning in rats (Maren et al, 1997), further indicating that dorsal hippocampus plays an important role in the Pavlovian fear conditioning in rats.…”
Section: Discussionsupporting
confidence: 92%
“…Possible optical artifacts from the camera were corrected through background subtraction. A calibration curve was created with the standards using a single regression equation (Jones and Gonzalez-Lima, 2001) in order to account for between-batch staining differences. These standards were linear in the 10 to 80 micron range of thickness used.…”
mentioning
confidence: 99%
“…The present study continues to emphasize the importance of hippocampal and parahippocampal regions in converging auditory (CS) and somatosensory (US) information. Another study on differential inhibition (Jones and Gonzalez-Lima, 2001a) showed decreased activity in the ventral cochlear nucleus in the differential inhibition group, which reflects changes in the learned signal value of the tone. Similarly in LI, the learned signal value of the tone decreases as the tone becomes an irrelevant stimulus that does not provide any new information about the environment.…”
Section: Discussionmentioning
confidence: 94%
“…Zonal analyses of cytochrome oxidase activity of lesions in the unilateral lesion model (group x lesion zone) were done with factorial ANOVA with staining batch as a covariate. Differences in interregional functional interactions were calculated according to the method of Jones and Gonzalez Lima (2001). Pearson correlations between cytochrome oxidase activity in the regions of interest were obtained.…”
Section: Methodsmentioning
confidence: 99%